Defensoria pública e sua legitimidade à tutela jurídica dos direitos humanos - Silva, Paulo Maycon Costa da (2012)
The realization of human rights is a prerequisite to the development of peoples, this requires legal mechanisms and techniques to its consistent and effective promotion, protection and fulfillment. So, agree that there is an institution or public agency created for the purpose of protecting those who suffer most in the face of human rights violations: the needy. In Brazil, among other institutions and public agencies, the responsibility of the Public Defender to promote the protection of human rights. The constitutional system recognizes the institution in its essence the role of the state court, whose duty is to provide guidance and legal defense of the needy. The legal system as a whole sufraga the relevance of the Ombudsman as a mainspring of human rights. In the prison system, with the ultimate regulatory changes, such as Law 12.313 of 2010 which introduced changes to the Law 7.210 of 1984, the institution must ensure the correct and humane enforcement of sentences and the security measures pertaining to the needy. With the Complementary Law 132 of 2009, to systematize other duties of the Public Defender, highlighting their contribution to the movement of access to justice. Within the OAS, to adopt Resolution 2656, 2011, characterizing, with ruler and compass, the relevance of the Ombudsman access to justice and protection of human rights. In this step, the present study concerns the role of Defender in the legal protection of human rights, through monographic and deductive methods, as there remains a technical and theoretical connection between these two points themed legal phenomenon, since the rights humans, especially after the second half of the twentieth century, form the basis of the legal system of the major Western nations in the world. This led, therefore, the emergence of technical and legal institutions aimed at realizing human rights. This applies to the Defender. Access to justice and public service provision of legal assistance are human rights, therefore, essential to humans and necessary for social inclusion. Countries such as Brazil, marked by social inequality, depend on the structuring of institutions like the Defender, designed to promote citizenship to the Brazilian people